Noises in the Blood : Orality, Gender, and the"Vulgar" Body of Jamaican Popular Culture - Cooper, Carolyn, 1950- (Book collections on Project MUSE., 1995)
The language of Jamaican popular culture-its folklore, idioms, music, poetry, song-even when written is based on a tradition of sound, an orality that has often been denigrated as not worthy of serious study. In Noises in the Blood, Carolyn Cooper critically examines the dismissed discourse of Jamaica's vibrant popular culture and reclaims these cultural forms, both oral and textual, from an undeserved neglect. Cooper's exploration of Jamaican popular culture covers a wide range of topics, including Bob Marley's lyrics, the performance poetry of Louise Bennett, Mikey Smith, and.